2003
DOI: 10.1074/jbc.m206831200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Molecular Characterization of a Chitinase from the Hard Tick Haemaphysalis longicornis

Abstract: A cDNA encoding tick chitinase was cloned from a cDNA library of mRNA from Haemaphysalis longicornis eggs and designated as CHT1 cDNA. The CHT1 cDNA contains an open reading frame of 2790 bp that codes for 930 amino acid residues with a coding capacity of 104 kDa. The deduced amino acid sequence shows a 31% amino acid homology to Aedes aegypti chitinase and a multidomain structure containing one chitin binding peritrophin A domain and two glycosyl hydrolase family 18 chitin binding domains. The endogenous chit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 48 publications
2
54
0
1
Order By: Relevance
“…This protein was expressed and purified from the culture medium of Sf9 cells infected with a recombinant baculovirus containing this cDNA. The purified H. longicornis chitinase had a size of 116 kDa, which was Ϸ12 kDa larger than the theoretical value, glycosylated and enzymatically active (22). These observations suggest that at least some of the larger-sized chitinases are indeed catalytically active and do not require proteolytic processing to yield enzymatically active proteins.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This protein was expressed and purified from the culture medium of Sf9 cells infected with a recombinant baculovirus containing this cDNA. The purified H. longicornis chitinase had a size of 116 kDa, which was Ϸ12 kDa larger than the theoretical value, glycosylated and enzymatically active (22). These observations suggest that at least some of the larger-sized chitinases are indeed catalytically active and do not require proteolytic processing to yield enzymatically active proteins.…”
Section: Discussionmentioning
confidence: 70%
“…In the tick, a similar large protein was also identified in vivo by 2D immunoblot analysis. The protein contains two ''ELR'' motifs and appears to be a chitinase of the chemokine family, which is involved in angiogenesis (22).…”
Section: Discussionmentioning
confidence: 99%
“…This result means that the rCHT1-immunized mice sera impacted on molting step. Previously, we cloned the H. longicornis CHT1 gene using the plaque screening methods, and revealed that the recombinant CHT1 is glycosylated which able to degrade chitin [24]. Chitinase is induced by ecdysteroids to degrade the older chitin at the time of molting [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Chitinase is induced by ecdysteroids to degrade the older chitin at the time of molting. Previously, we cloned a gene encoding 113 kDa protein (CHT1) of Haemaphysalis longicornis, and identified the CHT1 as a protein of chitinase (You et al 2003). In this study, the recombinant CHT1 (rCHT1) expressed in Escherichia coli was used to immunize mice.…”
mentioning
confidence: 99%
“…Preparation of recombinant H. longicornis serine proteinase: Expression and purification of rHlSP was carried out as previously described [18]. Briefly, the coding region of catalytic domain of the HlSP gene was inserted into the pTrcHis B plasmid (Invitrogen, CA., U.S.A.) and transformed into E. coli (Top10F', Invitrogen) following standard techniques.…”
Section: Methodsmentioning
confidence: 99%